Mixed agreements revisited : the EU and its member states in the world - Hillion, Christophe; Koutrakos, Panos (Modern studies in European law ;, 2010)
Mixed agreements are one of the most significant and complex areas of EU external relations law. They are concluded by the Member States and the EU (or the European Community in the pre-Lisbon days) with third countries and international organisations. Their negotiation, conclusion and implementation raise important legal and practical questions (about competence, authority, jurisdiction, responsibility) and often puzzle not only experts in countries and organisations with which the EU works but also European experts and students. This book, based on papers presented at a conference organised.